Oxidation Behavior of Hf-Modified Aluminide Coatings on Inconel-718 at 1050°C - Wang, Yongqing; Suneson, Marc; Smialek, James L. (Journal of Coating Science and Technology, 2014)
Simple β-NiAl, Hf-modified β-NiAl, Pt-diffused, Pt-modified β-(Ni,Pt)Al + ξ-PtAl2, and Hf-Pt-modified β-(Ni,Pt)Al were cyclic oxidation tested at 1050°C in air on Inconel-718 substrates for up to 4370h. The Pt-diffused specimen failed most quickly, < 100 h, while the simple β-NiAl aluminide maintained a positive weight change for 1300 h. The Pt-modified aluminides clearly improved the cyclic oxidation behavior of both simple and Hf-modified aluminides, sustaining a zero weight change only after 3600 and 4000 h, respectively. The Hf additions did not immediately appear to produce as strong an improvement as expected, however, they were more highly ranked when normalized by coating thickness. They also decreased surface rumpling, important for TBC durability. Hf-rich NiAl grain boundaries, formed during coating processing, resulted in HfO2 particles in the scales and oxide pegs at the metal interface, all suggesting some level of over-doping. The high sulfur content of the substrate influenced spalling to bare metal and re-healing to less protective Ni(Al,Cr)2O4 spinel-type and (Ti,Cr,Nb)O2 rutile scales. The evolution of these surface features have been documented over 100 to 4370 h of exposure. The coating aluminum content near failure was 2-3 wt. %.